Influence of Host’s Selling Strategy on Customers’ Product Return Intention in Livestreaming Online Commerce - Linh, Do Trang; Park, Min Jae (Journal of Internet Commerce, 2025)
This study investigates the relationship between live-stream hosts’ sales strategies and viewers’ intention to return purchased products. Using the stimulus-organism-response (S-O-R) model and partial least squares structural equation modeling, we analyzed 242 survey responses from Vietnam to examine post-purchase behavior in live-stream shopping. Findings reveal that transactional selling approaches—focusing on price and promotion—can heighten impulsive buying tendencies, which in turn increase product dissonance and the likelihood of returns. Conversely, relationship-oriented strategies that provide rich product information and foster trust reduce perceived risk and discourage product returns. The results highlight the importance of balancing sales pressure with trust-building tactics to mitigate negative post-purchase outcomes in live commerce.
Keywords: Host’s selling strategy; livestreaming commerce; product return intention; SOR model; Vietnam